1991
DOI: 10.1101/gad.5.12b.2567
|View full text |Cite
|
Sign up to set email alerts
|

DNA-binding properties of the HMG domain of the lymphoid-specific transcriptional regulator LEF-1.

Abstract: Lymphoid enhancer-binding factor 1 (LEF-11 is a pre-B and T lymphocyte-specific nuclear protein that participates in the regulation of the T-cell antigen receptor (TCR) a enhancer by binding to the nucleotide sequence 5'-CCTTTGAA. LEF-1 protein shares with the nonhistone high mobility group protein 1 (HMG-1) and several transcriptional regulators a single region of amino acid homology, termed the HMG box, which has been implicated in DNA binding. Here, we report the biochemical analysis of the interaction of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
240
1
3

Year Published

1993
1993
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 262 publications
(259 citation statements)
references
References 41 publications
15
240
1
3
Order By: Relevance
“…This region coincides with a stretch of basic amino acids located C-terminal to the HMG box proper, which has been shown to contribute to the affinity of binding in several studies (4,40,41), and more recently has been found to increase the bending angle of a DNA motif complexed to the Lef-1 HMG box (10). Our deletion and footprinting data on the Ste11 HMG box indicate that the C-terminal basic region mediates recognition of the A 11 A 12 3' flank sequence.…”
Section: Discussionmentioning
confidence: 99%
“…This region coincides with a stretch of basic amino acids located C-terminal to the HMG box proper, which has been shown to contribute to the affinity of binding in several studies (4,40,41), and more recently has been found to increase the bending angle of a DNA motif complexed to the Lef-1 HMG box (10). Our deletion and footprinting data on the Ste11 HMG box indicate that the C-terminal basic region mediates recognition of the A 11 A 12 3' flank sequence.…”
Section: Discussionmentioning
confidence: 99%
“…The known properties of HU, HMG1, and HMG2 are distinct from their sequence-specific counterparts: IHF in bacteria and LEF1 (the clearest example) in mammals. Both IHF and LEF-1 bind and bend DNA at specific recognition sites (Robertson and Nash 1988;Thompson and Landy 1988;Yang and Nash 1989;Giese et al 1991Giese et al ,1992. The binding of LEF-1 or the presence of intrinsically curved DNA can functionally substitute for IHF in the phage ~ intasome reaction (Goodman and Nash 1989; Giese et al 1992;Goodman et al 1992).…”
Section: Discussionmentioning
confidence: 99%
“…This conservation presumably accounts for the similar properties of various members of the HMG-box protein family. The insensitivity of UBF to major groove modifications coupled with its sensitivity to the minor groove binding drugs distamycin A, chromomycin A3 and actinomycin D suggests that UBF may be a minor groove binding protein as determining factor), TCF1 (T-Cell Factor-1), and LEF-1 (Lymphoid Enhancer Factor) (41,42). The DNA binding specificity of different HMG-box proteins is presumably dictated by variant amino acids displayed on the DNA binding surface(s) (47,48).…”
Section: Methodsmentioning
confidence: 99%